Time-dependent chronoamperometric response of dual inlaid disk electrodes - Bell, Christopher G.; Howell, Peter D.; Stone, Howard A. (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2013)
[Display omitted] ► Analytical formula for chronoamperometric current at dual inlaid disk electrodes. ► Valid over long-time scales when diffusion layers have started to overlap. ► Valid when centre-to-centre disk separation is much larger than disk radii. ► Quasi-reversible reactions, unequal diffusion coefficients and unequal disk radii. ► Explicit expressions for generator–collector currents and collection efficiency. Dual-disk electrodes allow for novel electrochemical investigations, particularly when used in generator–collector mode. However analytical understanding of how the current response of each individual electrode is affected by the presence of the neighbouring electrode is limited. In this article, we derive an approximate analytical solution for the time-dependent chronoamperometric current response of a pair of electrodes, each subjected to a different initial potential step. The solution is valid when the centre-to-centre distance between the disks is much larger than the disk radii, and for times such that the diffusion layers generated at each electrode have started to interact. It accommodates quasi-reversible reactions and unequal diffusion coefficients of the oxidant and the reductant. The generator–collector system is a specific case, and we deduce simple expressions for the time-dependent current and steady-state collection efficiencies at each electrode. The analytical solution facilitates analysis of shielding and feedback effects, and shows the explicit dependence of the currents on the underlying electrochemical parameters.